Effect of Leflunomide on the Abnormal Expression of Lipid Rafts and F-Actin in B Lymphocytes from Patients with Systemic Lupus Erythematosus - Guang Fu Dong; Xiao Zhang; De Ning He; Ling Li; Guang Feng Zhang (Journal of Immunology Research)
Purposes. To investigate the possible changes in B cell subsets and in B cell expression patterns of lipid rafts (LRs) and F-actin in patients with SLE and whether leflunomide treatment may have effect on these changes. Methods. The B cell subsets and LRs expression were determined by flow cytometry and confocal microscopy, and F-actin expression was examined by confocal microscopy. Results. CD27+IgD+ B cell subsets were significantly decreased while CD38+CD95+ B cell subsets increased in SLE patients. The LRs levels of B cells were remarkably increased and positively correlated with SLEDAI and anti-dsDNA titer in SLE patients. The expression level of LRs was significantly higher in CD38+ B cells than CD38− B cells and negatively correlated with C3 levels. The increased expression of LRs was associated with reduced expression of F-actin in the B cells from active SLE patients. Furthermore, in vitro treatment of the cells with A771726 reduced the expression level of LRs, attenuated the overaggregation of LRs, and normalized the distribution of F-actin. Conclusions. There were abnormalities in B cell subsets and LRs and F-actin expression of B cell from SLE patients. Modulation of B cell expression of LRs and F-actin by LEF could be a potential therapeutic target for SLE.